APPLICATIONS TO PREDICT CHILDREN'S COMPUTER ABILITY USING MICROSOFT VISUAL BASIC 6.0 - Andreas Anggoro Noevida Soesantho; Diyah Ruri Irawati, SKom, MMSI (Jurnal Sistem Informasi, 2004)
Scientific writing is about Application Ability To Predict Child Through Computers,where the author tries to present how to predict a child by computer with the aim todevelop thinking skills and the speed of a child. In this scientific writing, theapplication child's ability to predict through computer using the programminglanguage Visual Basic 6.0 object-oriented in order to be able to utilize existingfacilities in it.